The battle for God responding to the challenge of Neotheism - Geisler, Norman L. 1932-; House, H. Wayne; Herrara, Max (Grand Rapids, MI Kregel, 2001)
Includes bibliographical references and index.
Keywords: God; Theology, doctrinal